2014
DOI: 10.1016/j.ydbio.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback regulation of Wnt signaling via N-linked fucosylation in zebrafish

Abstract: Summary L-fucose, a monosaccharide widely distributed in eukaryotes and certain bacteria, is a determinant of many functional glycans that play central roles in numerous biological processes. The molecular mechanism, however, by which fucosylation mediates these processes remains largely elusive. To study how changes in fucosylation impact embryonic development, we up-regulated N-linked fucosylation via over-expression of a key GDP-Fucose transporter, Slc35c1, in zebrafish. We show that Slc35c1 overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 115 publications
1
18
0
Order By: Relevance
“…Meanwhile, Feng et al reported that during the development of zebrafish, SLC35C1 negatively regulated Wnt signalling through N‐fucosylation of Wnt8a and Lrp6, and overexpression of SLC35C1 disrupts embryonic patterning in a transporter activity‐dependent manner. Interestingly, this group also found that at the same time, SLC35C1 expression is modulated by canonical Wnt . This suggests that the Wnt signalling pathway is a carefully regulated system and it may limit its activity via elevated expression of SLC35C1.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, Feng et al reported that during the development of zebrafish, SLC35C1 negatively regulated Wnt signalling through N‐fucosylation of Wnt8a and Lrp6, and overexpression of SLC35C1 disrupts embryonic patterning in a transporter activity‐dependent manner. Interestingly, this group also found that at the same time, SLC35C1 expression is modulated by canonical Wnt . This suggests that the Wnt signalling pathway is a carefully regulated system and it may limit its activity via elevated expression of SLC35C1.…”
Section: Discussionmentioning
confidence: 90%
“…23,24 The current study implicates SLC35C1 as a negative regulator for the canonical Wnt pathway during this process. We dis- 26 This suggests that the Wnt signalling pathway is a carefully regulated system and it may limit its activity via elevated expression of SLC35C1.…”
Section: Discussionmentioning
confidence: 92%
“…[6] To our knowledge there has been only one report from our previous study where MOE was employed to control a specific signaling pathway, in which we discovered that enhanced fucosylation on N-glycans inhibits Wnt signaling. [7] …”
mentioning
confidence: 99%
“…[5] MOE remodels glycan structures by supplementing the growth media with carbohydrate analogues that get incorporated into glycans by the endogenous biosynthetic machinery. [7] Nevertheless,m odification of cell-surface glycans using genetic or MOE approaches are not free of limitations:due to the functional redundancyo fm any glycosyltransferases, typically more than one gene needs to be knocked out in order to produce ap henotype, [8] and gene editing of glycosyltransferases may also introduce unexpected side effects,f or example,c haperone functions. [7] Nevertheless,m odification of cell-surface glycans using genetic or MOE approaches are not free of limitations:due to the functional redundancyo fm any glycosyltransferases, typically more than one gene needs to be knocked out in order to produce ap henotype, [8] and gene editing of glycosyltransferases may also introduce unexpected side effects,f or example,c haperone functions.…”
mentioning
confidence: 99%
“…[6] To our knowledge there has been only one report from our previous study where MOE was employed to control aspecific signaling pathway,inwhich we discovered that enhanced fucosylation on N-glycans inhibits Wnt signaling. [7] Nevertheless,m odification of cell-surface glycans using genetic or MOE approaches are not free of limitations:due to the functional redundancyo fm any glycosyltransferases, typically more than one gene needs to be knocked out in order to produce ap henotype, [8] and gene editing of glycosyltransferases may also introduce unexpected side effects,f or example,c haperone functions. [9] Likewise,M OE often leads to changes on diverse array of glycans.Therefore, there is ac ritical need to explore alternative approaches for the modification of cell-surface glycans.…”
mentioning
confidence: 99%